Hubungan Pola Makan dan Tingkat Stres dengan Kejadian Dispepsia pada Pasien Dewasa di RSUD Lakipadada - Hayuti Windha Pagiu; Lucia Yogyana Suramas; Serli Serli (Jurnal Kesehatan Amanah, 2024)
Background: Diet and stress levels are one of the causes of dyspepsia. Dyspepsia is upper abdominal discomfort associated with digestive disorders. Research Objective: To determine the relationship between diet and stress levels with the incidence of dyspepsia in adult patients. The research design used was a cross sectional approach, with a purposive sampling technique, namely 46 respondents using the Chi-Square statistical test at a significance level of α=0.05. Research Results: With the Chi-Square statistical test using SPSS, there was a significant relationship between eating patterns and dyspepsia in adult patients at Lakipadada Hospital. The p-value = 0.003 was obtained, where of the 46 respondents whose eating patterns were irregular, 19 respondents experienced severe dyspepsia. . Meanwhile, 7 (75.0%) respondents who had a regular eating pattern experienced severe dyspepsia. There is a significant relationship between the level of stress and the incidence of dyspepsia in adult patients at Lakipadada Regional Hospital, with a p-value = 0.004, where 20 (76.9%) respondents experienced severe stress and severe dyspepsia, while respondents experienced mild stress and mild dyspepsia. as many as 14 (70.0%) respondents Conclusion: There is a relationship between diet and stress levels with the incidence of dyspepsia in adult patients at Lakipadada Regional Hospital. Patients are expected to maintain their diet and stress levels.